Suraj mukhi - Samina, Raza (Book Group Karachi, 2002)
Suraj Mukhi is a popular Urdu textbook series used in Pakistani schools, particularly for primary and secondary levels. This series is designed to introduce students to the rich and diverse world of Urdu literature. It covers a wide range of topics, including poetry, prose, grammar, and vocabulary.